A Genome-Wide Association Study of Nausea Incidence in Varenicline-Treated Cigarette Smokers. Issue 10 (13th March 2021) - Chenoweth, Meghan J; Lerman, Caryn; Knight, Jo; Tyndale, Rachel F
Abstract: Introduction: Varenicline is the most efficacious smoking cessation treatment; however, long-term cessation rates tend to be <25%. Nausea, the most common side effect of varenicline, observed in 28% of individuals treated, peaks early following treatment initiation and reduces cessation success. Genetic variation influences treatment response, however genetic contributors to individual differences in side effects are less understood. Methods: We conducted a genome-wide association study of nausea incidence at 1 week following the initiation of varenicline treatment (corresponding to the target quit date) in 189 cigarette smokers of European ancestry (NCT01314001). Additive genetic models examining the likelihood of experiencing any versus no nausea controlled for population substructure, age, and sex. Variants with minor allele frequencies (MAF)≥10% were considered. Results: Fifty-seven (30.2%) out of 189 participants reported nausea. The top variant associated with nausea was rs1568209 (odds ratio [OR] = 2.61 for A vs. G allele; 95% confidence interval [CI] = 1.65, 4.15; p = 2.1e-7; MAF = 48.7%), mapping to the SLCO3A1 drug transporter gene on chromosome 15. In the same trial, rs1568209 was not associated with nausea in either the nicotine patch ( p = .56; n = 181) or placebo ( p = .59; n = 174) arms. In varenicline-treated smokers, the incidence of nausea was higher in females (44.6%; n = 74) versus males (20.9%; n = 115) ( p = .001), however there was no evidence of a difference in the influence of rs1568209 on nausea between the sexes ( p for sex*genotype interaction = .36). Future studies in larger samples are required to test the robustness of this finding. Conclusions: Variation in SLCO3A1 may influence the risk for developing nausea in varenicline-treated smokers, which may alter adherence and cessation. Implications: Varenicline-associated nausea reduces adherence and limits cessation success. Previous candidate gene association studies showed genetic factors influence nausea on varenicline. This pilot genome-wide investigation of nausea, the most common side effect associated with varenicline treatment and an important cause of treatment discontinuation, suggests the potential involvement of common variation in the SLCO3A1 drug transporter gene.